Pronator teres rupture in a recreational tennis player - Moya-Torrecilla, Francisco; Garcia-Gutierrez, Guillermo; Medina-Porqueres, Ivan (Faculty of Education – University of Travnik, Bosnia & Herzegovina, 2021)
A pronator teres lesion is a relatively uncommon sports injury often associated with a stroke and/or hit traumatic mechanism, and only reported in cricket and golf contexts. Herein we present an unusual case of pronator teres rupture in an amateur tennis player with a forehand stroke mechanism, including the diagnostic process and the approach. The patient presented to our facilities complaining of right anterior forearm tightness and pain. The clinical presentation was confirmed by magnetic resonance imaging (MRI). Conservative treatment was chosen and consisted of a relative rest followed by rehabilitative treatment until the patient returned to his previous activity four weeks post-injury. Pronator teres strains are the possible causes of forearm pain and tightness and can be related to tennis-specific actions.
Keywords: Brazos - Músculos - Tratamiento; magnetic resonance imaging; forearm; pronator teres muscle; Strain; Muscle injury